2017
DOI: 10.1891/1078-4535.23.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Performance and National Council Licensure Examination for Registered Nurses Outcomes: Field Research Perspectives

Abstract: Simulation has been broadly accepted as a powerful educational tool that may also contribute to verification of student achievement of program outcomes and readiness for the RN role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Eight theories/models appeared in more than one article (Table 3 ); many theories were used once in one of the reviewed articles. Tanners clinical judgement model was frequently found in this review (Brackney et al, 2017 ; Eisenmann, 2021 ; Gonzalez et al, 2021 ). Similarly, Gonzalez et al ( 2021 ) and Hensel and Billings ( 2019 ) discussed the NCSBN Clinical Judgement Measurement Model (NCJMM) and referred to the originality of Tanner's clinical judgement model.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Eight theories/models appeared in more than one article (Table 3 ); many theories were used once in one of the reviewed articles. Tanners clinical judgement model was frequently found in this review (Brackney et al, 2017 ; Eisenmann, 2021 ; Gonzalez et al, 2021 ). Similarly, Gonzalez et al ( 2021 ) and Hensel and Billings ( 2019 ) discussed the NCSBN Clinical Judgement Measurement Model (NCJMM) and referred to the originality of Tanner's clinical judgement model.…”
Section: Resultsmentioning
confidence: 75%
“…Authors identified risk factors outside the classrooms and even before starting the nursing programme and reacted based on identified weaknesses (Sanderson et al, 2022 ). Similarly, Brackney et al ( 2017 ) and Moniyung ( 2015 ) utilized Astin's input‐environment‐outcome model. The input includes student characteristics upon admission (Moniyung, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations